ADVANTAGES AND DEVELOPMENT PROGRESS OF MODERN ELECTRIC CARS (ResearchJet Journal of Analysis and Inventions, 2023)
This article cites the negative impact of road cars on the environment, its consequences, the popularization of modern types of electromobiles and its advantages. Moreover, in our country, the latest innovations in the field of electric cars and measures for the further development of this industry will be discussed.